2020
DOI: 10.14740/jnr602
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Nervous System - Neurological Manifestations in Patients With COVID-19: A Systematic Review

Abstract: Coronavirus (CoV) is a virus infectious disease with a considerable spectrum of clinical presentations. Symptoms ranged from asymptomatic infection to severe pneumonia that may lead to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and several clinical complications. Neurologic symptoms related to CoV have been described recently in the literature. The relationship between SARS-CoV-2 and the central nervous system (CNS) is still not clear. This review aimed to reveal the current knowledge regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Among hospitalized children fever, chills and gastrointestinal symptoms prevail, whereas cough and respiratory signs are less common [Kim L. 2020]. It has been established that the SARS-CoV-2 virus has neuroinvasive properties [Iadecola C 2020, Severo Bem Junior L 2020. Neurologic complications such as malaise, headache and anosmia are common in all age groups, but more severe: dizziness, altered mental status, ischemic strokes, encephalopathy, and encephalitis have also been Here we present a unique case of fatal, fulminant acute hemorrhagic encephalitis in a SARS-CoV-2 infected infant.…”
Section: Introductionmentioning
confidence: 99%
“…Among hospitalized children fever, chills and gastrointestinal symptoms prevail, whereas cough and respiratory signs are less common [Kim L. 2020]. It has been established that the SARS-CoV-2 virus has neuroinvasive properties [Iadecola C 2020, Severo Bem Junior L 2020. Neurologic complications such as malaise, headache and anosmia are common in all age groups, but more severe: dizziness, altered mental status, ischemic strokes, encephalopathy, and encephalitis have also been Here we present a unique case of fatal, fulminant acute hemorrhagic encephalitis in a SARS-CoV-2 infected infant.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple studies have addressed the frequency and characteristics of neurological dysfunction among COVID-19 patients, ( 28 , 29 ) but there is still a substantial gap in knowledge in several domains, specifically regarding critically ill patients. Both central and peripheral nervous system involvement have been extensively reported in ICU patients, either as a manifestation of systemic critical illness or its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reported COVID-19 cases with neurological manifestations tend to occur more frequently in severe infections and in older people with comorbidities, such as diabetes mellitus (DM) and hypertension [5,9]. It has been reported that SARS-CoV and MERS-CoV coronaviruses were detected in the CSF of a patient with encephalitis and acute respiratory distress syndrome [10], and these viruses along with COVID-19 have ACE-2 receptors on the respiratory epithelial cells, glial cells, neurons, and vascular endothelium [5,6], which may indicate that COVID-19 possibly target and damage the nerve tissues.…”
Section: Discussionmentioning
confidence: 99%